Visual evoked potentials to a diamond pattern can predict accommodation power more accurately than those to a checkerboard pattern - Ryota Yamamoto; Shozo Tobimatsu; Kiyoka Miyahara; Takeshi Yoshitomi (PLoS ONE, 2026)
Purpose Visual evoked potentials (VEPs) are significantly influenced by the spatial frequency (SF) and angular distribution of visual stimuli. Here, we examined the effects of retinal blur on VEPs with changes in refractive power, to determine whether VEPs can be used as an index of objective accommodation (OA). Methods Twenty-one university students with corrected visual acuity of at least 0.0 logMAR participated in the study. Checkerboard (Check) and Check rotated 45° (Diamond) patterns were used as the visual stimuli. Pattern reversal VEPs were recorded from the uncyclopleged dominant eye. Changes in P100 latency and amplitude were assessed by concave-lens loading to obtain OA. Near and far points of accommodation were determined using a visual display terminal near-point meter to obtain subjective accommodation (SA). Linear regression analysis between SA and OA was performed. Results P100 amplitudes were affected by the refractive power even when the P100 latency of VEPs was unaffected. VEPs to Diamond more precisely predicted OA than those to Check: SA was 11.70 ± 3.15 D (mean ± SD) whereas the OAs to Diamond and Check were 5.05 ± 1.15 D and 4.74 ± 1.62 D, respectively, with SA being significantly higher ( p < 0.01). A significant positive correlation was found between SA and OA for Diamond ( r = 0.64, p = 0.003) and between SA and OA for Check ( r = 0.54, p = 0.016). Conclusions VEPs to Diamond predicted the refractive power more accurately than those of Check due to a better fit. Visual resolution is better in response to vertical and horizontal stimuli than oblique ones (orientation effect). Because the fundamental SF component of Check, but not Diamond, lies in the 45° and 135° (oblique) orientations, VEPs to Check are more susceptible to retinal blur, probably due to the orientation effect. SA had significantly greater accommodation values than OA due to the different methodologies.